Displaced anterior cruciate ligament avulsion fractures: Arthroscopic staple fixation - Sundararajan, S R (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Anterior cruciate ligament (ACL) avulsion fracture is commonly associated with knee injuries and its management is controversial ranging from conservative treatment to arthroscopic fixation. The aim of our study was to assess the clinical and radiological results of arthroscopic staple fixation in the management of ACL avulsion fractures. MATERIALS AND METHODS: Twenty-two patients (17 males and 5 females) who underwent arthroscopic staple fixation for displaced ACL avulsion fractures were analysed. The mean age was 32.2 years (15-55 years) with a mean followup of 21 months (6-36 months). All patients were assessed clinically by calculating their Lysholm and International Knee Documentation Committee (IKDC) scores and the radiological union was assessed in the followup radiographs. RESULTS: The mean Lysholm score was 95.4(83-100) and the mean IKDC score was 91.1(77-100) at the final followup. In 20 patients anterior drawer's test was negative at the end of final followup while two patients had grade I laxity. Associated knee injuries were found in seven cases. The final outcome was not greatly influenced by the presence of associated injuries when treated simultaneously. At final followup all the patients were able to return to their pre-injury occupation CONCLUSION: Arthroscopic staple fixation is a safe and reliable method for producing clinical and radiological outcome in displaced ACL avulsion fractures.